A J curve of interprofessional change: co-locating non-health partners in an oncology unit. (13th February 2020) - Young, Jenny; Snowden, Austyn
Abstract : Background: Internationally, clinicians face increased demand, pressure on resources and unmet patient needs. A community social support service was co-located within cancer clinics in Glasgow, Scotland to help address some of these needs. Aim: To analyse the impact of the service on clinical staff and to propose an explanatory theory of change. Method: Qualitative exploratory design, using thematic analysis of semistructured interviews with 8 nurse specialists and 2 medical oncologists from lung, breast, head and neck, and gastrointestinal oncology teams in Glasgow in 2018–2019. Findings: Four themes captured this process: 'The conversation', 'A better experience', 'Freedom to focus' and 'Working hand in hand'. Conclusion: Together, these four themes explained the process of effective interprofessional working. This process would have been predicted by the J-curve literature on diffusion of innovations. Linking J-curve theory to this successful process provides new understanding that could prove essential for clinical teams who are implementing change within their practice.